A case controlled study examining the bladder microbiome in women with Overactive Bladder (OAB) and healthy controls. (July 2017) - Curtiss, Natasha; Balachandran, Aswini; Krska, Louise; Peppiatt-Wildman, Claire; Wildman, Scott; Duckett, Jonathan
Abstract: Objective: To characterise the microbiome in healthy women with no bladder symptoms and to compare this to the bladder microbiome in patients with overactive bladder syndrome (OAB). Study design: MSU specimens from 63 women with OAB were compared to urine from 35 controls. Urine was centrifuged and the resulting sediment pellet was re-suspended in supernatant and plated under aerobic conditions for 48 h and anaerobic conditions for 7 days. Each morphologically distinct colony was purity plated. Bacterial colonies were lysed and polymerase chain reaction undertaken to amplify the 16 s ribosomal RNA gene. This DNA was purified and sequenced allowing identification of bacterial genera. Results: The mean number of different bacterial genera was 5.0 in both controls and OAB patients (p = 0.99). The uropathogenic bacteria Proteus (P = 0.01) was more commonly isolated from women with OAB. The genus lactobacillus was present less commonly in urine from OAB patients when compared to urine taken from controls (p = 0.02). Overall the most commonly grown bacteria were staphylococcus (grown in 59% of samples), streptococccu s (51%), corynebacterium (37%) and lactobacillus (28%). A total of 95 different genera were identified from the urine samples. Conclusion: The female human bladder has a diverse microbiome with stastistically significant differences between bacterial species present in OAB patients and controls.